Chromatin to Clinic: The Molecular Rationale for PARP1 Inhibitor Function - Feng, Felix Y.; de Bono, Johann S.; Rubin, Mark A.; Knudsen, Karen E. (Molecular cell, 2015)
Poly(ADP-ribose) polymerase 1 (PARP1) inhibitors were recently shown to have potential clinical impact in a number of disease settings, particularly as related to cancer therapy, treatment for cardiovascular dysfunction, and suppression of inflammation. The molecular basis for PARP1 inhibitor function is complex, and appears to depend on the dual roles of PARP1 in DNA damage repair and transcriptional regulation. Here, the mechanisms by which PARP-1 inhibitors elicit clinical response are discussed, and strategies for translating the preclinical elucidation of PARP-1 function into advances in disease management are reviewed. Poly(ADP-ribose) polymerase 1 (PARP1) inhibitors were recently shown to have clinical impact in a number of disease settings. In this Perspective, the mechanisms by which PARP1 inhibitors elicit clinical response are discussed, and strategies for translating the preclinical elucidation of PARP1 function into advances in disease management are reviewed.